Physical and sensory quality of coffee dried in three prototypes of greenhouse solar dryers - Huamán-Murillo, María; Mejía, Shirley; Murillo-Baca, Silvia; Ponce-Rosas, Fortunato; Fuentes-Meza, Maria (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Reducing the drying time of coffee without causing negative effects on cup quality has been the subject of several investigations. The objective was to determine the effect of three variants of a greenhouse-type solar dryer prototype on the physical, sensory and microbiological quality of coffee. The solar dryer prototype with three variants, prototype 1 (P1) greenhouse solar dryer, prototype 2 (P2) solar dryer with air extractor and prototype 3 (P3) solar dryer with air extractor and solar powered heaters, was compared to traditional drying (T0) (cement floor). Drying time, physical grain defects, yield, sensory and microbiological quality were evaluated. The best results were obtained in P3 with a drying time of 52 h (2 ¼ days), with dry parchment coffee beans without primary defects, higher yield in exportable gold coffee (83.24 %), sensory profile of 84.25 points qualified as specialty coffee (with Q Premium grade) and better safety than coffee obtained by traditional drying; demonstrating that the greenhouse type solar dryer with air extractor and solar energy heaters is a sustainable alternative to improve the efficiency of coffee drying while preserving its sensory quality, an essential value for producers to achieve better prices.